Monitoring in analiza zaraščanja kraške krajine v GIS okolju - Hočevar, Milan (Zbornik gozdarstva in lesarstva, 2004)
This article presents Karst landscape spontaneous afforestation research. Remote sensing techniques, multitemporal analyses of satellite images in the GIS environment and statistical regression models were used in the research. Since 1935, the abundance of forests in this area has increased from 50.4% to 67.9%. About 71% of variability was explained with a regression model. Spontaneous afforestation is strongly influenced by the following factors: altitude, distance to the forest edge, share of afforested area in previous time periods, share of agricultural land, and two variables describing the intensity of agricultural use. Although various demographical, socio-economic and agro-structural factors were analysed in this research study, their influence on the process of spontaneous afforestation could not be established. If there are no significant changes in the processes of spontaneous afforestation in the future,forest abundance can be expected to increase to 72.5% by the year 2020.
Keywords: GIS; gozdarstvo; Kras; zaraščanje